2017
DOI: 10.1007/jhep11(2017)031
|View full text |Cite
|
Sign up to set email alerts
|

Stiff phases in strongly coupled gauge theories with holographic duals

Abstract: According to common lore, Equations of State of field theories with gravity duals tend to be soft, with speeds of sound either below or around the conformal value of v s = 1/ √ 3. This has important consequences in particular for the physics of compact stars, where the detection of two solar mass neutron stars has been shown to require very stiff equations of state. In this paper, we show that no speed limit exists for holographic models at finite density, explicitly constructing examples where the speed of so… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 43 publications
(78 reference statements)
1
44
0
Order By: Relevance
“…Hence, in the intermediate density regime the speed of sound most likely has to exceed the conformal value. There have been suggestions in the literature that the conformal limit may be an absolute upper bound, but counterexamples have been pointed out within the gauge/string duality [88,89]. Values larger than c 2 s > 1/3 are routinely reached in phenomenological models of nuclear matter or in extrapolations of low-density effective theories, but in these calculations the speed of sound typically behaves monotonically and cannot be traced into the chirally symmetric phase.…”
Section: Speed Of Soundmentioning
confidence: 99%
“…Hence, in the intermediate density regime the speed of sound most likely has to exceed the conformal value. There have been suggestions in the literature that the conformal limit may be an absolute upper bound, but counterexamples have been pointed out within the gauge/string duality [88,89]. Values larger than c 2 s > 1/3 are routinely reached in phenomenological models of nuclear matter or in extrapolations of low-density effective theories, but in these calculations the speed of sound typically behaves monotonically and cannot be traced into the chirally symmetric phase.…”
Section: Speed Of Soundmentioning
confidence: 99%
“…The applications of the gauge/gravity duality to quark-gluon plasma has been a very active field [1,2]. Very recently these techniques have also been applied in the context of neutron stars [3,4] and stiff phases of matter [5,6] which are likely to be needed to achieve large enough stars [7]. In [4], a holographic model dual to N = 4 super-Yang-Mills and quenched supersymmetric matter was studied, and it was observed that neutron stars can only accommodate very small amounts of quark matter.…”
Section: Introductionmentioning
confidence: 99%
“…In [58] it was demonstrated that the original D3-brane background (the dual to N = 4 SYM theory), supplemented with flavor D7-brane probes (introducing quenched quark matter) at finite chemical potential, provides a realistic equation of state for cold and dense quark matter. This realization paved the road for further investigations [59][60][61][62].…”
Section: Discussionmentioning
confidence: 82%